Effects of virtual reality on psychophysical measures of pain: superiority to imagination and nonimmersive conditions - Tesarz, Jonas; Herpel, Christopher; Meischner, Meike; Drusko, Armin; Friederich, Hans-Christoph; Flor, Herta; Reichert, Julian (Pain, 2024)
Virtual reality (VR) has been shown to be effective in pain management. However, to date, little is known about the mechanisms by which immersive experiences influence pain processing. The aim of this study was to investigate the direct effects of an immersive VR environment on the perception of experimental pain in individuals with chronic pain and pain-free controls. The immersion in a VR landscape was compared with mental imagery and a nonimmersive control condition. Using a randomized within-crossover design, pressure pain detection and tolerance thresholds, spatial and temporal summation (SSP, TSP), and conditioned pain modulation (CPM) were measured in 28 individuals with chronic pain and 31 pain-free controls using phasic cuff pressure on the legs. Direct comparison between the groups showed that although individuals with pain had significantly lower pain thresholds, reduced CPM effects, and increased TSP, the VR condition had the same pain-inhibitory effect on pain thresholds as in pain-free controls. Conditioned pain modulation effects were reduced by all conditions compared with baseline. There were no significant differences between conditions and baseline for TSP and SSP. Overall, pain modulatory effects were largest for VR and smallest for imagery. These results demonstrate that immersion in a VR environment has an increasing effect on pain thresholds, reduces pain inhibition in a CPM paradigm, and has no effects on TSP. This applies for participants with chronic pain and pain-free controls. These VR effects exceeded the effects of mental imagery on the nonimmersive control condition. This indicates that VR effectively modulates pain perception in both patients and controls irrespective of differences in pain perception.
Gesehen am 08.01.2025